Long-term results of immediate implantation in the maxillary molar area with simultaneous sinus floor elevation by the crestal approach and early loading protocol: A retrospective case series follow-up study - Nader Ayubian Markazi; Nasrin Akhondi; Mostafa Montazeri (Tabriz University of Medical Sciences, 2018)
Background. This study aimed to determine the long-term survival rate of implants placed in fresh sockets of extracted maxillary molars with simultaneous sinus floor elevation and early loading protocol. Methods. Nineteen maxillary molar teeth were extracted by tooth sectioning, and the sockets were debrided. Drilling for implant placement (Either Xive, Dentsply or Axiom, Antogyr) was terminated 1 mm short of the sinus floor with a pilot drill. Then, according to Summers' technique, elevation of the Schneiderian membrane and bone grafting were performed. The implants were placed according to non-submerged procedure after sinus grafting and preparation of the desired osteotomy site. Results. The implants had been in function up to 5 years and the mean time of loading was 33.12 months. Analysis of crestal bone loss records indicated a mean of -0.054±0.56 mm of bone resorption (with a range of -0.86 to +0.90 mm). The amount of crestal bone resorption on the mesial and distal surfaces of implants was -0.02±0.559 mm and -0.09±0.59 mm, respectively (P=0.232). Survival rates and success rates were 100% and 95.45%, respectively. Conclusion. Immediate implant placement in the posterior maxilla with simultaneous sinus floor augmentation and early loading was a reliable and predictable approach.